(3QSGdI aj GdEeGeIs - (3eMeO Hf Rjf GdOjf gdGd GdMfaj,J (B1012 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GHJdi NdjdN MSf Cdbi Ydjg cdGekG hHYO ajbhd eMeO Hf CMeO GdTgjQ HGHf gdGd GYde Cfg dG jNai Ydi Phi GdCdHGf GdSGdcjf LGOI GdUhGH Cf CYXe GdeTGb gh JcGdja eG dG jWGb s
(3BNQgG (B:s
(3R hgh EKfGf ai NeSI VdG aMUd YTQ hCNHQc HCf eLehY GdMGUdjf GKfGf hYTQhf ajchf ai GdHOGA GdjSQi hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B4s
(3GdfSNI HgG MhGTs
(3HChdg fbhd eNJdaIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B266) s
Keywords: (3GdeLGejYs